Hemophagocytic Syndrome Associated with Mycoplasma pneumoniae Pneumonia - Yuji Koike; Nao Aoki (Case Reports in Pediatrics)
Mycoplasma pneumoniae (Mp) sometimes causes immunological complications in children. We present a rare case of hemophagocytic syndrome (HPS) caused by Mp in a previously healthy 7-year-old Japanese girl. A chest radiograph obtained to evaluate the source of her fever showed infiltration in the lower right lung with mild splenomegaly. We could diagnose the patient with HPS on the basis of the hemophagocytic-lymphohistiocytosis- (HLH) 2004 criteria. She met the criteria for fever, splenomegaly, neutrophil count (<1,000/μL), platelet count (<10.0 × 104/μL), fasting triglyceride level (>265 mg/dL), and ferritin level (>500 ng/mL). Furthermore, a peripheral blood smear showed an increased number of monocytes/macrophages with erythrophagocytosis. Treatment with clarithromycin and prednisolone, which was initiated soon after the diagnosis, was successful. Mp infection might partly progress to HPS in certain conditions. Clinicians should be aware of HPS caused by Mp and start appropriate treatment as soon as possible if the disease is suspected.